BET protein function is required for inflammation: Brd2 genetic disruption and BET inhibitor JQ1 impair mouse macrophage inflammatory responses - Belkina, Anna C. (2013)
Histone acetylation regulates activation and repression of multiple inflammatory genes known to play critical roles in chronic inflammatory diseases. However, proteins responsible for translating the histone acetylation code into an orchestrated pro-inflammatory cytokine response remain poorly characterized. Bromodomain extra terminal (BET) proteins are “readers” of histone acetylation marks with demonstrated roles in gene transcription, but the ability of BET proteins to coordinate the response of inflammatory cytokine genes through translation of histone marks is unknown. We hypothesize that members of the BET family of dual bromodomain-containing transcriptional regulators directly control inflammatory genes. We examined the genetic model of brd2 lo mice, a BET protein hypomorph, to show that Brd2 is essential for pro-inflammatory cytokine production in macrophages. Studies that utilize siRNA knockdown and a small molecule inhibitor of BET protein binding, JQ1, independently demonstrate BET proteins are critical for macrophage inflammatory responses. Furthermore, we show that Brd2 and Brd4 physically associate with the promoters of inflammatory cytokine genes in macrophages. This association is absent in the presence of BET inhibition by JQ1. Finally, we demonstrate that JQ1 ablates cytokine production in vitro and blunts the “cytokine storm” in endotoxemic mice by reducing levels of IL-6 and TNF-α while rescuing mice from LPS-induced death. We propose that targeting BET proteins with small molecule inhibitors will benefit hyper-inflammatory conditions associated with high levels of cytokine production.